Partisipasi Publik Dalam Perumusan Kebijakan Penataan Ruang Dan Dampaknya Pada Pengelolaan Sumber Daya Air Di Kota Tanjungpinang - Hendro Sulistiyo; Wulandari, Florentina Ratih; Subiyakto, Rudi (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Human activities have a significant impact on the environment, so spatial planning policies are needed. The rules instruct that spatial planning be carried out innovatively involving the public. Spatial planning for water resources is the substance of the spatial planning policy. The purpose of this study was to determine the condition of public participation in the process of formulating spatial planning policies and in the management of Water Resources, and to determine the impact of public participation in the process of formulating spatial planning policies on the management of Water Resources. Field review as the main focus of the study with a qualitative descriptive study method. Informants from related stakeholders, namely the government, community, and entrepreneurs (private) were divided into 3 groups. Informants were determined using the purposive sampling technique, and continued with the snowball sampling technique. Data collection methods were through interviews, observations and documentation. The level of public participation was analyzed according to the typology of the eight Arnstein Participation Ladders. The results of the study showed that in the process of formulating spatial planning policies in Tanjungpinang City, the community was involved at the consultation level (fourth ladder) and included in the category of degree of tokenism. Public participation in the management of Water Resources was at the partnership level (sixth ladder) included in the category of degree of citizen power. The conclusion of the study was that the role of the public in the formulation of spatial planning policies is relatively suboptimal. This participation condition has an impact on public participation in the management of Water Resources.